Jalur Penyelesaian Sengketa Perbankan Syariah - Inna Fauzi; Nabila Rizki (SALIHA: Jurnal Pendidikan & Agama Islam, 2021)
Sharia banking disputes are often encountered in social life. This has led to the emergence of various regulations that are made and are binding in an effort to apply order to social life. This basis allows researchers to raise the theme of settling Sharia banking disputes by using data obtained from various articles, journals of scientific papers as well as standardized provisions, regulations and legal bases to later serve as the basis for the theoretical basis. The purpose of this research is to find out the solutions that the author can offer in solving various kinds of economic hazards. The method used in writing uses a qualitative method with qualitative descriptive research. Qualitative descriptions by collecting data related to the focus of economic dispute resolution in the religious courts, such as through peace, arbitration, deliberation, and through courts (litigation). In addition, the presentation of various examples of dispute cases that occur in the world of Islamic banking, as well as the proper sequence of settlement steps. The result of the research is that there are stages in resolving Sharia banking disputes at the Religious Courts. Settlement The first step is through the mediation channel which has a more in-depth description including the need for a mediator and who is entitled to become a mediator in the mediation process. Some of the legal basis for the provisions here are also explained to strengthen assumptions, and as a legal basis that has been established and patented by the relevant government. The next thing is that before a dispute occurs, it must first be known about the contract carried out by both parties to the dispute